Aggregate stock liquidity of Bursa Malaysia / Liew Ping Xin - Liew , Ping Xin (2020)
Liquidity plays a crucial role in the functioning of secondary stock markets. However, little is known about the liquidity condition and how trading activities of different investor groups affect liquidity in the Malaysian stock exchange. This thesis focuses on three aspects of Malaysian stock market liquidity, namely, aggregate liquidity in the context of foreign equity flows, higher-order statistical moments of liquidity in the context of proprietary day trading, and, the liquidity connectedness of stock, bond, money and foreign exchange markets. First, this thesis examines the impact of gross foreign equity inflows on aggregate liquidity in a Vector Autoregression framework using newly assembled foreign trading data over the period from October 2009 to December 2016. Based on the best performing bid-ask spread proxy for Malaysian stocks – Closing Percent Quoted Spread (CPQS), a one-way causality from gross foreign equity inflows to aggregate liquidity is detected. The participation of foreign investors erodes the stock market liquidity. Uncertainties in the U.S. markets negatively affect aggregate liquidity through the flows of foreign institutions, whose positive feedback trading destabilizes the local bourse. Despite the shocks, there is sufficient liquidity provision from local state-backed institutional funds and local proprietary day traders. Second, capitalizing on the availability of trade data of proprietary day traders (PDTs), the liquidity effect of PDTs’ trading is empirically assessed in a Generalized Autoregressive Conditional Heteroskedasticity (GARCH) framework using daily data spanning October 2012 to June 2018. Higher PDTs’ trade volume promotes aggregate liquidity, and this is attributable to intense competition among informed traders. However, such improved liquidity comes at the expense of higher conditional volatility and conditional skewness of CPQS. The former is due to the exchange-imposed immediacy for PDTs to close their open positions, whereas the latter can be attributed to the exclusive intraday short selling rights granted to PDTs. Lastly, this thesis computes both static and time-varying liquidity connectedness indices of four financial asset markets – stock, bond, money and foreign exchange using daily data spanning from July 2005 to December 2018. The analysis reveals that liquidity connectedness is severely underestimated in the static framework. In the time-varying framework, total liquidity connectedness of the four asset markets is significantly responsive to market events. The foreign exchange market emerges as the main transmitter as well as receiver of liquidity spillovers. The liquidity connectedness surges during crisis periods such as the Global Financial Crisis. Spillovers are the strongest for volatility connectedness, followed by return connectedness and lastly, liquidity connectedness.